(untitled) (Global Journal of Computer Science and Technology, 2013)
Unstructured peer-to-peer file sharing networks are very popular in the market Which they introduce Large network traffic The resultant networks may not perform search efficiently and effectively because used overlay topology formation algorithms are creating unstructured P2P networks are not performs guarantees In this paper we choosen the square-root topology and show that this topology Which improves routing performance compared to power-law networks In the square-root topology shows that this topology is optimal for random walk searches A power-law topology for other types of search techniques besides random walks Then we interoduced a decentralized algorithm for forming a square-root topology its effectiveness in constructing efficient networks using both simulations and experiments with our prototype Results show that the square-root topology can provide a good and the best performance and improvement over power-law topologies and other topology types